(untitled) (Applied Biological Research, 2017)
In present study ten isolate of Pseudomonas, isolated from rice rhizosphere,haracterized on the basis of morpho-biochemical and molecular characteristics. Screening of their plant growth promoting activities viz., siderophore production, proteolytic activity, ammonia production, IAA production and HCN production revealed that the isolate PfAs1 was most promising one with highest siderophore production (6.18 cm dia. of yellow halo) and proteolytic activity (5.85 cm dia. halo zone). The results showed that none of the isolates possessed all the tested PGP activities. IAA and ammonia production was determined quantitatively for all the isolates. The IAA and ammonia production in tested Pf strains ranged from 15.66 to 48.58 and 179.05 to 394.72 mg L-1. The phylogenetic analysis using 16S rRNA gene sequences showed phylogenetic position of different fluorescent Pseudomonads. The results revealed that the isolated strains were Pseudomonas fluorescens and P. putida.